EFFECT OF PUPILLARY DILATATION ON THE ANTERIOR CHAMBER DEPTH BETWEEN MYOPIC AND HYPERMETROPIC EYES (Journal of Medical & Health Sciences Review, 2025)
Purpose:Pupillary dilation is used for retinal examinations, for diagnosis of glaucoma, macular degeneration and intraocular procedures such as cataract, retinal and vitreous surgeries. The current study sought to determine how pharmacological pupil dilation altered the anterior chamber depth (ACD) in myopic and hypermetropic eyes.Methodology:In this prospective, comparative observational study the participants were divided into two groups: myopes (≥ -1.0 D) and hypermetropes (≥ +1.0 D). ACD was evaluated with contact optical biometry and calculation was done by Sanders–Retzlaff–Kraff/theoretical (SRK/T). Pupillary dilation was induced by 1% tropicamide, and ACD was evaluated 30 minutes later. Mean changes were compared within and between groups using paired and independent t-tests.Results:The average anterior chamber depth (ACD) before pupillary dilation was considerably deeper in myopic eyes compared to hypermetropic eyes (3.4 ± 0.2 mm versus 3.0 ± 0.2 mm; p < 0.01). Following dilation, both groups exhibited a significant increase in anterior chamber depth (myopic: +0.12 ± 0.04 mm; hypermetropic: +0.20 ± 0.05 mm; p < 0.01 for each). From the initial value the ACD was increased more in hypermetropic eyes with p value less than 0.05 between the groups.Conclusion:ACD was deepened with dilation in both myopic and hypermetropic eyes. Hypermetropic eyes showed comparatively more deepening. These parameters are important for predicting risk of glaucoma, calculation of power of intraocular lens, and surgeries involving anterior segment.